Injil Papat Inkulturasi Kitab Suci Dalam Budaya Jawa - Kristhalia Dessindi (Jurnal Teologi Kontekstual Indonesia, 2022)
The challenge of inculturating the gospel with cultural traditions is not new. The presence of Catholicism in Java is quite influenced by Javanese culture, both literature, art, tradition and others. One of the inculturation efforts is the translation of the Holy Scriptures into Javanese, as has been done by Father Soenarja, SJ. Efforts to translate the Bible into the local language pave the way for wide inculturation for the development of the faith of the people of the Bible. So, the translation of the text of the Bible also takes into account the benefits of building the faith of the people. One of the efforts made is that the translation of the Holy Scriptures is not only in language but also adapted to the form of literature that is familiar to the Javanese in conveying a teaching, one of which is macapat. By using C.S Pierce's semiotic analysis approach, the author finds that the Papat Bible has an interpreter and ground that can be used as a mission bridge in Javanese culture. Through C.S Pierce's semiotic analysis, Papat's Bible, which has many choices of diction, can be interpreted through the feelings of Javanese culture through liturgical pastoral efforts for the sake of living the faith of the Javanese.